2006
DOI: 10.1038/sj.ejcn.1602433
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity in Italian adults 2004, and an overview of trends since 1983

Abstract: Objective: Overweight has been increasing in several developed countries over the last few decades. No update information on the issue is available for Italy. Design and setting: We conducted a computer assisted personal in-house interview survey in March-April 2004, on a sample of 2932 Italian individuals (1407 men and 1525 women) aged 18 years or over, representative of the general adult Italian population. Information on weight and height was self-reported. Results: Overall, 3.4% of the Italian adult popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
46
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 56 publications
(70 reference statements)
8
46
1
Order By: Relevance
“…Among the young these data confirmed a favourable pattern, since obesity prevalence in Italians aged 19-34 years was about 5 %, which is lower than that of other countries (34) . Moreover, the results confirmed that males had a prevalence of obesity slightly higher than that of females (24,33) . The present study suggests that obesity may be associated with some FRL dimensions.…”
Section: Underweightsupporting
confidence: 75%
See 1 more Smart Citation
“…Among the young these data confirmed a favourable pattern, since obesity prevalence in Italians aged 19-34 years was about 5 %, which is lower than that of other countries (34) . Moreover, the results confirmed that males had a prevalence of obesity slightly higher than that of females (24,33) . The present study suggests that obesity may be associated with some FRL dimensions.…”
Section: Underweightsupporting
confidence: 75%
“…Obesity rates are low in Italy (9 %) relative to most countries in the Organisation for Economic Co-operation and Development (23,24) , but the trend has been increasing in recent years. Focusing on this country, the objective of the present study was to compare obese v. non-obese consumers in terms of their general food-related lifestyles and to explore possible food-related factors affecting obesity in Italy.…”
mentioning
confidence: 99%
“…1,2 In the past two decades, the prevalence of obesity has increased dramatically in both developing and developed countries, 3,4 thus rendering obesity the sixth most important risk factor contributing to the overall burden of human disease worldwide. Family, twin and adoptee studies demonstrated that genetic factors significantly contribute to the etiology of obesity, with heritability ranging from 0.3 to 0.8.…”
Section: Introductionmentioning
confidence: 99%
“…There is no doubt, that becoming overweight or obese takes many years perhaps decades, although obesity is often present in childhood and adolescence [7,8,9,10,11]. Genetic factors, lifestyle and social elements, diversity of cultural and economic background could be important as well, but mainly nutritional habits alone or combined with sedentary lifestyle are the real reasons for growing fat [4,12,13]. Weight change during old age often remains unexplored [12,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic factors, lifestyle and social elements, diversity of cultural and economic background could be important as well, but mainly nutritional habits alone or combined with sedentary lifestyle are the real reasons for growing fat [4,12,13]. Weight change during old age often remains unexplored [12,14,15]. Weight gain is considered as part of the normal ageing process.…”
Section: Introductionmentioning
confidence: 99%